A Straightforward Decision Rule for Selecting Lower-of-Cost or Market Price: A Contraction. - Lindbeck, Rudolph S.; Rogow, Robert B.; De Coster, Don T. (The Accounting Review, 1975)
Abstract This article presents a straightforward decision rule for selecting an inventory valuation price at lower-of-cost or market. This decision rule avoids the complexities of decision tables and algebraic equations; thereby, allowing students of accounting to concentrate on mastering the concepts of lower-of-cost or market valuation. Accounting educators concerned with student achievement continually seek decision tables and algebraic equations which clarify or hasten an understanding of accounting concepts. Usually, such educators prefer straightforward decision rules which do as good as or better than these devices.